The Role of Phytochelatin Synthase in Phytoremediation Agent: Structural Conservation of Phytochelatin (PC) Synthase to Maintain Its Activity as Heavy Metal Detoxification in Plant - Vidayanti, Viky; Permatasari, Galuh Wening (Future Science, 2020)
Phytochelatin (PC) Enzyme has crucial role in heavy metal detoxification and homeostasis in plants. This study aimed to evaluate the genetic variation of PC synthase related to its activity based on structural comparison. We evaluated PC genes and protein sequences from 6 plants namely, Brassica sp., Amaranthus sp., Noccaea sp., Arabidopsis sp., Nicotiana sp., and Pteris sp. All sequences were aligned based on CLUSTALW matrix for DN sequences and MUSCLE algorithm for protein sequences. Data were clustered using MEGA Software for similarity clustering. Selected data were further modeled using SWISSMODEL to evaluate the 3D-structural analysis based on homology modeling. Thus, all protein models were superimposed and evaluated the structure comparison based on RMSD data. The result showed that genetic variation of PC gene is high among species. But it is clustered for the same species has similar sequence. In addition, protein sequences also showed the high diversity among species and it is still clustered based on their genus. RMSD data showed that PC synthase from 6 plant has similar structure and tend to conserved even there is genetic variation or amino acid modification. We concluded that structural of PC gene is more conserved than its sequences. It is important to keep its function among species.